The Effect of Compensation Equity and Social Work Environment on Employee Retention: The Mediating Effect of Job Satisfaction - Hemmy Fauzan; Tongku Rifa Ayu Pitaloka; Irhamsyah Putra; Bahrul Yaman; Suhendra Suhendra (Journal of Management and Business Innovations, 2025)
This study investigates the impact of compensation equity and the social work environment on employee retention, with job satisfaction serving as the mediating variable, among employees of PT JPT Jatidiri Trans. The employed quantitative method was path analysis utilizing data from 116 respondents. The study's results indicated that equitable compensation and a positive social work environment greatly enhanced job satisfaction, therefore leading to improved employee retention. The findings indicate that equitable remuneration and a conducive work environment substantially improve job satisfaction and employee retention. Organizations should prioritize equitable compensation and a conducive work environment to improve employee satisfaction and retention. Keywords: Compensation Employee Retention, Equity, Job Satisfaction, Social Work Environment